PENGARUH PERBANDINGAN SARI KULIT SEMANGKA (Citrullus lanatus (thunb.)) DENGAN SARI DAUN KELOR (Moringa oleifera) DAN KONSENTRASI KARAGENAN TERHADAP KARAKTERISTIK JELLY DRINK - Suliasih, Neneng Suliasih (Pasundan Food Technology Journal (PFTJ), 2023)
This research aims to obtain the right concentration of carrageenan and the ratio of watermelon rind juice to Moringa leaf juice to produce the best jelly drink characteristics. The benefit of this research is to increase the usability of watermelon rinds and Moringa leaves as a form of long-lasting processed food. Can increase local food productivity as food diversification. As well as providing information about making watermelon rind jelly drink with Moringa leaves. The experimental design used in this research was a randomized block design (RAK) with 9 treatments, each treatment repeated 3 times to obtain 27 experimental units. With the ratio factor of watermelon rind juice to moringa leaf juice p1 (1: 3), p2 (2 : 2), p3 (3 : 1) and the second factor is carrageenan concentration k1 (0.2%), k2 (0.25%), k3 (0.3%). The response in this research is a chemical response including determining potassium levels; Vitamin C; pH. Physical responses include viscosity; Syneresis; Color. Based on the research results, it shows that the ratio of watermelon rind juice to Moringa leaf juice has an effect on potassium levels, vitamin C levels, pH, viscosity and syneresis. The concentration of carrageenan affected pH, viscosity and syneresis, but had no effect on potassium and vitamin C levels. The interaction between the ratio of watermelon rind juice to Moringa leaves and the concentration of carrageenan had an effect on syneresis, but had no effect on potassium levels, vitamin C levels, pH and viscosity.